2016
DOI: 10.1002/cjce.22581
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the mixing and dispersing of floating particles in viscous system

Abstract: The effects of baffle configuration, impeller type, impeller diameter ratio, and immersion depth on the critical drawdown speed and power of floating particles were investigated by experiment, and the advantageous stirred vessel was determined on the basis of the low energy consumption principle. Furthermore, the effects of system viscosity, mean solid concentration, and particle size on the dispersing characteristic of floating particles were also researched with the advantageous stirred vessel. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It was mixed with the tangential flow near the center and generated the eccentric vortex. The position of the vortex observed in experiment (Liu et al, 2016), as shown in Figure 10, was basically the same where the largest intensity appeared in the simulation (Chen, 2015). 3The turbulence intensity near the surface in the vessel equipped with a Rushton turbine was larger than those in the vessels equipped with other impellers.…”
Section: Distribution Of Turbulence Intensitysupporting
confidence: 52%
“…It was mixed with the tangential flow near the center and generated the eccentric vortex. The position of the vortex observed in experiment (Liu et al, 2016), as shown in Figure 10, was basically the same where the largest intensity appeared in the simulation (Chen, 2015). 3The turbulence intensity near the surface in the vessel equipped with a Rushton turbine was larger than those in the vessels equipped with other impellers.…”
Section: Distribution Of Turbulence Intensitysupporting
confidence: 52%
“…This process is quite different from previous results in the literature. For example, Özcan-Taşkin et al [28] found that the drawdown position of floating particles is close to the vessel walls when a downward pumping impeller is mounted close to the vessel base, and Liu et al [40] found that an eccentric vortex is able to generate a strong vertical force to draw down floating particles. The main reason for the difference in drawdown positions and patterns is that the investigated flow conditions vary greatly; the flow fields in the literature are mainly turbulent, while they are laminar in this study.…”
Section: Phenomena Of Particle Drawdown From Top Surfacementioning
confidence: 99%
“…Te study by Atibeni et al [30], in which the width and shape of the bafes were varied, found that triangle bafes were more efective in suspending foating solids. Liu et al [31] studied the efect of the number of bafes on N JD and reported that N JD was lowest when one bafe was used. Furukawa et al [32] reported that N JD was reduced by placing a partial bafe away from the wall surface.…”
Section: Introductionmentioning
confidence: 99%